(untitled) (International Journal of Engineering and Computer Science, 2015)
Energy saving to prolong the network life is one of the major design issue while developing a new routing protocol for wireless sensor networks(WSNs). Clustering is key mechanism in large multi-hop wireless sensor networks for obtaining scalability, reducing energy consumptions and increase the life time of network to achieve better network performance. In literature various clustering approaches are proposed. In this article we present a survey on different energy efficiency clustering techniques and working of few of them and distinguish them according to operational mode and state of clustering.